2016
DOI: 10.1159/000447896
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling Exacerbates Keloid Cell Proliferation by Regulating Telomerase

Abstract: Objectives: Our goal was to investigate the relationship between keloid and telomerase as well as clarifying the influence of Wnt/β-catenin signaling on keloid cell proliferation. Methods: Tissues from 18 keloid patients were collected for further study. Keloid progenitor cells (KPC) and skin progenitor cells (SKP) were both included in this study. Lenti-virus transfection was used to divide cells into different groups in which cells were treated with different substances: negative control (NC) group, wnt10a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…It is believed that TGFb functions as an indirect mitogen by inducing the expression of other growth-promoting factors in fibroblasts, such as platelet-derived growth factor and basic fibroblast growth factor 2 (Zhang et al, 2017). In addition, Wnt/b-catenin and STAT3 pathways, as well as some micro-RNAs and long non-coding RNAs, have been reported to promote keloid fibroblast proliferation via different mechanisms (Chua et al, 2011;Feng et al, 2017;Lim et al, 2006;Park et al, 2008;Rang et al, 2016;Shi et al, 2018;Wu et al, 2014;Yu et al, 2016;Zhang et al, 2016). In the current study, we identified the TRAF4/p53 axis as a pathway that controls keloid fibroproliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that TGFb functions as an indirect mitogen by inducing the expression of other growth-promoting factors in fibroblasts, such as platelet-derived growth factor and basic fibroblast growth factor 2 (Zhang et al, 2017). In addition, Wnt/b-catenin and STAT3 pathways, as well as some micro-RNAs and long non-coding RNAs, have been reported to promote keloid fibroblast proliferation via different mechanisms (Chua et al, 2011;Feng et al, 2017;Lim et al, 2006;Park et al, 2008;Rang et al, 2016;Shi et al, 2018;Wu et al, 2014;Yu et al, 2016;Zhang et al, 2016). In the current study, we identified the TRAF4/p53 axis as a pathway that controls keloid fibroproliferation.…”
Section: Discussionmentioning
confidence: 99%
“…During the proliferative phase, TGFb stimulates fibroblast proliferation, collagen synthesis, and angiogenesis (Bettinger et al, 1996;Douglas, 2010;Lichtman et al, 2016). In addition to TGFb, Wnt/b-catenin signaling exacerbates keloid cell proliferation via regulating telomerase and increase fibronectin production (Chua et al, 2011;Yu et al, 2016), and STAT3 contributes to keloid pathogenesis by promoting collagen production, cell proliferation, and migration (Lim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among the bioprocesses investigated in the protein interaction network, we identified the negative regulation of the Wnt receptor signaling pathway. Through Wnt signaling, δ-catenin prevents Rho GTPase signaling, modulating the Ras superfamily in cytoskeletal reorganization (Lu et al , 2016). Perturbations in this pathway, observed after depletion of δ-catenin, may contribute to functional neurological alterations (Arikkath et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor-beta (TGF-beta)/Smad signaling plays a key role in excessive fibrosis and keloid formation [6] Wnt signaling also plays key roles in various cellular functions including proliferation, differentiation, survival, apoptosis and migration, [8] which can exacerbate keloid cell proliferation and inhibit keloid cell apoptosis through its interaction with telomerase [16]. …”
Section: Discussionmentioning
confidence: 99%